Respuesta :
Let me just rewrite the details in a more understandable manner
f(x) = 2x + 7
g(x) = 3x + c
f( g(x) ) = g( f(x) )
Proceeding to the problem, we have to find the value of c by making use of the relationship written by the third equation. The notation f( g(x) ) means that you have to replace x with g(x). So, you would have incorporate one equation to the other, and vice versa. By equating them, we can determine x. Let us start with f( g(x) ) .
f( g(x) ) = 2(3x + c) + 7
f( g(x) ) = 6x + 2c + 7
Next, we do the similar thing to g( f(x) ).
g( f(x) ) = 3(2x+7) + c
g( f(x) ) = 6x + 21 + c
Then, we equate both simplified equations
6x + 2c + 7 = 6x + 21 + c
Let's simplify further by placing c on one side, and the rest on the other side:
2c - c = 6x - 6x + 21 - 7
c = 14
f(x) = 2x + 7
g(x) = 3x + c
f( g(x) ) = g( f(x) )
Proceeding to the problem, we have to find the value of c by making use of the relationship written by the third equation. The notation f( g(x) ) means that you have to replace x with g(x). So, you would have incorporate one equation to the other, and vice versa. By equating them, we can determine x. Let us start with f( g(x) ) .
f( g(x) ) = 2(3x + c) + 7
f( g(x) ) = 6x + 2c + 7
Next, we do the similar thing to g( f(x) ).
g( f(x) ) = 3(2x+7) + c
g( f(x) ) = 6x + 21 + c
Then, we equate both simplified equations
6x + 2c + 7 = 6x + 21 + c
Let's simplify further by placing c on one side, and the rest on the other side:
2c - c = 6x - 6x + 21 - 7
c = 14
Answer:
14
Step-by-step explanation:
We have that
f(g(x)) = f(3x + c) = 2(3x + c) + 7 = 6x + 2c + 7,
and
g(f(x)) = g(2x + 7) = 3(2x + 7) + c = 6x + c + 21.
Hence, these functions are the same if and only if 2c + 7 = c + 21, so c = 14